Major Bleeding With Dabigatran and Rivaroxaban in Patients With Atrial Fibrillation: A Real-World Setting. (October 2014) - Fontaine, Gabriel V; Mathews, Katy D; Woller, Scott C; Stevens, Scott M; Lloyd, James F; Evans, R Scott
Background: Although the rate of bleeding among patients with atrial fibrillation (AF) taking novel oral anticoagulants in randomized controlled trials is described, the rate of bleeding with "real-world" use is uncertain. Methods: We conducted a retrospective electronic medical record interrogation and subsequent chart review among patients within Intermountain Healthcare between October 2010 and November 2012. Patients were included if they had a diagnosis of AF and were receiving either dabigatran or rivaroxaban. Rates of major bleeding were calculated. Results: Among 2579 patients, 13 (0.5%) experienced major bleeding (95% confidence interval [CI] 0.23-0.77), 5 (0.19%) experienced intracranial hemorrhage (95% CI 0.02-0.36), and 2 (0.08%) experienced fatal bleeding. Of the 13 patients experiencing a major bleed, 8 (61.5%) would have been excluded from the Randomized Evaluation of Long-Term Anticoagulation Therapy (RE-LY) and Rivaroxaban Once Daily Oral Direct Factor Xa Inhibition Compared with Vitamin K Antagonism for prevention of Stroke and Embolism Trial in Atrial Fibrillation (ROCKET AF) clinical trials. Conclusion: We observed a rate of major bleeding similar to that reported in randomized clinical trials among patients with AF prescribed dabigatran or rivaroxaban.